2015
DOI: 10.1007/s12274-014-0675-9
|View full text |Cite
|
Sign up to set email alerts
|

Facile production of ultrathin graphitic carbon nitride nanoplatelets for efficient visible-light water splitting

Abstract: Ultrathin graphitic carbon nitride nanoplatelets (UGCNPs) are synthesized by a facile manner via an efficient and eco-friendly ball milling approach. The obtained UGCNPs are 2-6 nm in size and 0.35-0.7 nm in thickness, with improved specific surface area over that of bulk graphitic carbon nitride. Photochemical experiments show that the UGCNPs are highly active in visible-light water splitting, with a hydrogen evolution rate of 1,365 μmol·h -1 ·g -1 , which is 13.7-fold greater than that of their bulk counterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(92 citation statements)
references
References 46 publications
(60 reference statements)
3
88
0
1
Order By: Relevance
“…Additionally, the broad band at 3500 cm −1 was assigned to the stretching mode of the hydroxyl group. Curiously, this band was strongest for the SCN sample, which may have resulted from slight oxidation of the g-C 3 N 4 by the strongly oxidizing sulfuric acid52. However, the presence of most of the characteristic bands in the acid-treated samples indicated that layered g-C 3 N 4 triazine bonds persisted and were perhaps only slight oxidized.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, the broad band at 3500 cm −1 was assigned to the stretching mode of the hydroxyl group. Curiously, this band was strongest for the SCN sample, which may have resulted from slight oxidation of the g-C 3 N 4 by the strongly oxidizing sulfuric acid52. However, the presence of most of the characteristic bands in the acid-treated samples indicated that layered g-C 3 N 4 triazine bonds persisted and were perhaps only slight oxidized.…”
Section: Resultsmentioning
confidence: 98%
“…Thus far, GCNNs prepared with various techniques, such as mechanical milling [24,25], chemical oxidation thermal or etching [20,26,27], physical and liquid exfoliation [22,28,29], and electrochemical synthesis [30] usually show wide distributions in both the number of layers and lateral size. In particular, due to many advantages of easy operation, low-cost, environmental benignity, and no reason for interfacial defects, liquid-phase exfoliation, usually in conjunction with ultrasonic treatment has been intensively explored for producing ultrathin GCNNs by delaminating bulk GCN [28,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Graphitic carbon nitride (GCN) is one of the most attractive materials, with excellent electrochemical properties [18,[24][25][26][27][28][29][30][31][32]. Furthermore, GCN can act as an electocatalyst in both OER and HER, but poor conductivity and a lack of redox site availability hamper the application of GCN-based materials.…”
Section: Introductionmentioning
confidence: 99%